A Multicenter Study of Bacterial Vaginosis in Women With or at Risk for Human Immunodeficiency Virus Infection. Issue 3 (2001) - Warren, Dora; Klein, Robert S.; Sobel, Jack; Kieke, Burney; Brown, William; Schuman, Paula; Anderson, Jean; Cu-Uvin, Susan; Mayer, Kenneth; Jamieson, Denise J.; Holmberg, Scott; Duerr, Ann
Abstract : Background: Bacterial vaginosis is a common gynecologic infection that has been associated with a variety of gynecologic and obstetric complications, including pelvic inflammatory disease, postabortal infection and premature delivery. Recent studies suggest that bacterial vaginosis may increase a woman's risk for human immunodeficiency virus (HIV). We undertook this study to assess whether the prevalence and characteristics of bacterial vaginosis differed according to HIV status in high-risk US women. Methods: Prevalence of bacterial vaginosis was assessed by Gram's stain and clinical criteria for 854 HIV-infected and 434 HIV-uninfected women enrolled in the HIV Epidemiology Research (HER) Study.Multiple logistic regression techniques were used to determine whether HIV infection independently predicted bacterial vaginosis. Results: Almost half (46%) the women had bacterial vaginosis by Gram's stain. The prevalence of bacterial vaginosis was 47% in the HIV-positive women compared with 44% in the HIV-negativewomen; this difference was not statistically significant (p = 0.36). After adjustment for other covariates, HIV-positive women were more likely than HIV-negative women to have bacterial vaginosis (odds ratio (OR) 1.31; 95% confidence interval (CI) 1.01-1.70) by Gram's stain but not by clinical criteria (OR 1.16; CI 0.87-1.55). Among HIV-positive women, use of antiretroviral drugs was associated with a lower prevalence of bacterial vaginosis (adjusted OR 0.54; Cl 0.38 -0.77). Conclusions: In this cross-sectional analysis of high-risk US women, HIV infection was positively correlated with bacterial vaginosis diagnosed by Gram's stain.